Unraveling the Personality Profile of the Sexual Murderer - Beauregard, Eric (Journal of interpersonal violence, 2021)
Although sexual homicide offenders (SHOs) evince personality disorders, few prior studies have examined all personality disorders or utilized control groups of offenders. Drawing on data from 616 adult male sex offenders including 85 who were SHOs, the current study examined the personality profile of the SHOs, by comparing them with a group of violent nonhomicidal sex offenders (VNHSOs) and a group of nonhomicidal sex offenders (NHSOs) on clinical diagnostics of personality disorders and various crime characteristics. The personality profile of SHOs is comprised primarily of Schizoid and Borderline Personality Disorders, and these offenders were significantly likely to select a victim, use a weapon, and use drugs and alcohol before their offenses, but less likely to force their victim to engage in sexual acts or humiliate them. The comorbidity of Schizoid, Borderline, and Antisocial Personality Disorder features presents unique personality dysfunction that facilitates the lethal sexual violence of SHOs relative to their nonhomicidal sexual offender peers.